Frequency of Systolic and Diastolic Dysfunction in Patients Presenting with Liver Cirrhosis Secondary to Hepatis-C at Tertiary Care Hospital, Karachi - Gul, Lubna; Jabeen, Rakshanda; Ejaz, Ayesha; Soniya; Guriya; Muhammad Zubair (Indus Journal of Bioscience Research, 2025)
Objective: To determine the frequency of systolic and diastolic dysfunction in patients presenting with liver cirrhosis secondary to hepatis C at Tertiary Care Hospital, Karachi. Methods: This cross-sectional study included 173 patients with liver cirrhosis admitted to a tertiary care hospital. Systolic and diastolic dysfunction were evaluated using echocardiography, with systolic dysfunction defined as an ejection fraction <55% and diastolic dysfunction identified by E/A ratio <1. Clinical parameters, including age, gender, cirrhosis duration, and Child-Pugh classification, were analyzed for their relationship with cardiac dysfunction. Results: Systolic dysfunction was present in 26.6% of patients, while 21.4% exhibited diastolic dysfunction. There were no significant associations between cardiac dysfunction and age, gender, cirrhosis duration, or Child-Pugh classification (p > 0.05). These findings suggest that cardiac dysfunction in cirrhosis develops independently of disease severity. Conclusion: Cirrhotic cardiomyopathy is common and may be underdiagnosed in cirrhotic patients, regardless of clinical severity. Routine cardiac screening, including echocardiography and ECG, should be considered for all cirrhotic patients to detect early dysfunction and prevent complications. Further research is needed to explore long-term outcomes and potential therapeutic strategies.